2021
DOI: 10.1111/adj.12870
|View full text |Cite
|
Sign up to set email alerts
|

A state‐wide study of dental comorbidities in psychiatric disorders resulting in avoidable emergency department presentations

Abstract: Background: Attendances at emergency departments (EDs) for dental conditions are unnecessary and come at a significant cost to health services. Methods: A population-based record-linkage analysis of a retrospective cohort over 2 years across state-based facilities in Queensland. This was to determine if people with mental illness were more likely than the general population to attend EDs for a range of non-traumatic or avoidable dental conditions. Results: There were 1 381 428 individuals in the linked databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Queensland also had the highest prevalence of psychiatric conditions (22.7%) in Australia, with an overall prevalence of 20.1% (Australian Bureau of Statistics, 2022 , 2018 ). Tellingly, data (Kisely et al, 2015 , 2021 ; Kisely & Lalloo, 2021 ) from the state's hospitals revealed that dental conditions accounted for the third most common reason for hospitalization in people with psychiatric conditions, and people with a history of psychiatric treatment were 72% more likely than the rest of the population to present to emergency departments with an avoidable dental condition.…”
Section: Discussionmentioning
confidence: 99%
“…Queensland also had the highest prevalence of psychiatric conditions (22.7%) in Australia, with an overall prevalence of 20.1% (Australian Bureau of Statistics, 2022 , 2018 ). Tellingly, data (Kisely et al, 2015 , 2021 ; Kisely & Lalloo, 2021 ) from the state's hospitals revealed that dental conditions accounted for the third most common reason for hospitalization in people with psychiatric conditions, and people with a history of psychiatric treatment were 72% more likely than the rest of the population to present to emergency departments with an avoidable dental condition.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25][26] MH conditions are related to increased edentulism, 27 reduced oral healthcare services utilization, 28,29 more missed appointments, 29 increased risk of inappropriate dental treatments, 30 and generational influences on children's toothbrushing behaviors. 31 To address these comorbidities, some authors 25,32 suggest a closer association between dental, primary, and MH care providers, which could increase access to care, reduce difficulty in receiving care, and focus on holistic care.…”
Section: Introductionmentioning
confidence: 99%